Identidade, resgate mnemônico de trauma e Künstlerroman em "Olho de gato", de Margaret Atwood - Capparelli, Fernanda dos Passos (2022)
In this dissertation, I discuss the concept of memory associated with identity construction, in addition to approaching other themes, such as trauma, gender studies and Künstlerroman, in Cat's eye, a novel by Canadian Margaret Atwood. With this, my intention was to reflect, through the narrative of the protagonist, Elaine, on the memorialistic and identity (re)construction that a character undertakes, after the city in which he lived for many years. Among Elaine's memories, there are memories of my perversities that she experienced in childhood, evolving from gender oppressions, a focus of discussion. In addition, as the protagonist is a painter, I also research the formation of the character as an artist, explaining about a term of German origin: the Künstlerroman. For all this journey, I raise theories about memory, which is the thematically central to the novel, in addition to associating it as a theme of identity, first space and trauma, which are worked on in the chapter of this dissertation. In the second chapter, I work with a gender, as it is a critical novel in relation to the specific oppressions of the female gender, and also evokes the author's locus of enunciation. The sequence of the second chapter also addressed the concept of Künstlerroman, thinking about the formation of the protagonist character, who is an artist. Moreover, watch this concept added to authorship, reflecting on the female particularities of the character addressed. Therefore, the theoretical foundation of this research has names such as: Maurice Halbwachs (1990), Aleida Assmann (2016), Michael Pollak (1992), Joël Candau (2016), among others, in memorials and identity; Judith Butler (2003), Simone de Beauvoir (1967) and Naomi Wolf (2020), in discussions of gender oppression; Eliane Campello (2003) and Jorge Santana (2003) regarding the questions about the Künstlerroman; in addition to Seligmann-Silva (2008), Jeanne Marie Gagnebin (2009) and Luis Kancyper (1994), for the discussion of trauma.